2014
DOI: 10.1111/ejss.12218
|View full text |Cite
|
Sign up to set email alerts
|

Glomalin‐related soil protein in French temperate forest soils: interference in the Bradford assay caused by co‐extracted humic substances

Abstract: Thermostable soil protein, known as glomalin, is an important component of soil carbon stocks. Thought to originate from endomycorrhizal fungi, Glomales, this operationally-defined fraction of soil organic matter contains proteins of diverse origin as well as non-protein material, including humic substances. Accumulation results from the balance between production/release and subsequent degradation. Quantification of the protein is subject to uncertainty because of the co-extraction of other components that in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 37 publications
3
19
0
Order By: Relevance
“…This indicates that interaction between added BSA and soil components, assumed to be polyphenols, had more effect on the spectrum at wavelength 595 nm than at 465 nm. The much greater estimate of GRSP with the standard addition accords with a previous study of forest soil where we reported a two‐ to sixfold increase in estimated GRSP with the standard addition method (Jorge‐Araújo et al, ). Furthermore, there was no tendency for the estimated GRSP to level off at the greatest dilution for the direct assay.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…This indicates that interaction between added BSA and soil components, assumed to be polyphenols, had more effect on the spectrum at wavelength 595 nm than at 465 nm. The much greater estimate of GRSP with the standard addition accords with a previous study of forest soil where we reported a two‐ to sixfold increase in estimated GRSP with the standard addition method (Jorge‐Araújo et al, ). Furthermore, there was no tendency for the estimated GRSP to level off at the greatest dilution for the direct assay.…”
Section: Resultssupporting
confidence: 90%
“…Attempts to do this have been largely unsuccessful, with very small yields; however, yields are rarely given in published reports. Jorge‐Araújo et al () postulated that irreversible, possibly co‐valent, bonds are formed between soil proteins and polyphenols during the high‐pressure, high‐temperature extraction. If this is the case, soil protein and added BSA might not experience the same interference.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…) and were also reported by previous reports ( Rosier et al, ; He et al, ). About 15% of soil N were from GRSP contribution ( Jorge‐Araújo et al, ), and GRSP‐N relations were reported as soil [N (g kg −1 ) = 0.004GRSP+0.1069, R 2 = 0.558] ( Fokom et al, ). In this paper, stepwise regression and SEM analysis showed non‐direct effects of soil N on GRSP amounts in soil (Tab.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, easy extractable GRSP (EE‐GRSP) and total GRSP (T‐GRSP) fraction can be distinguished, depending on the chosen extraction procedures. The concept of glomalin has been faced with criticism due to the uncertainty about the chemical characterization, co‐extraction of non‐protein material and the doubts regarding the origin of this soil organic fraction ( Jorge‐Araújo et al, ). However, glomalin can be still viewed as an operationally‐defined part of more persistent soil organic matter with evidenced relationships to soil quality and mycorrhiza ( Wu et al, ; Vasconcellos et al, ).…”
Section: Introductionmentioning
confidence: 99%